What happens when employers are obliged to nudge? Automatic enrolment and pension saving in the UK - Jonathan Cribb; Carl Emmerson (Institute for Fiscal Studies (IFS), 2016)
This paper studies the first nationwide introduction of automatic enrolment, in which employers in the United Kingdom are obliged to enrol employees into a workplace pension scheme, which employees can then choose to leave if they wish. We exploit the phased rollout of automatic enrolment since 2012 to estimate its effect on pension saving. As a result of automatic enrolment, participation in workplace pensions among eligible private sector workers is estimated to have increased by 37 percentage points, and workplace pension membership reached 88% amongst those affected by April 2015. Automatic enrolment significantly increased the average pension contribution rate, in part because some newlyenrolled employees received an employer contribution well above the minimum mandated by the government. Furthermore, many employees who did not have to be automatically enrolled were nonetheless brought into a workplace pension scheme as a result of the policy. We find no evidence of employers reducing employer contributions for newly-hired employees or existing members of workplace pensions.
Keywords: J32; D14; J38; 330; automatic enrolment; private pensions; non-wage benefits